Impact of NK Cell Activating Receptor Gene Variants on Receptor Expression and Outcome of Immunotherapy in Acute Myeloid Leukemia - Hussein, Brwa Ali; Hallner, Alexander; Wennström, Lovisa; Brune, Mats; Martner, Anna; Hellstrand, Kristoffer; Bernson, Elin; Thorén, Fredrik B. (Frontiers in Immunology, 2021)
Natural killer cells are important effector cells in the immune response against myeloid malignancies. Previous studies show that the expression of activating NK cell receptors is pivotal for efficient recognition of blasts from patients with acute myeloid leukemia (AML) and that high expression levels impact favorably on patient survival. This study investigated the potential impact of activating receptor gene variants on NK cell receptor expression and survival in a cohort of AML patients receiving relapse-preventive immunotherapy with histamine dihydrochloride and low-dose IL-2 (HDC/IL-2). Patients harboring the G allele of rs1049174 in the KLRK1 gene encoding NKG2D showed high expression of NKG2D by CD56bright NK cells and a favorable clinical outcome in terms of overall survival. For DNAM-1, high therapy-induced receptor expression entailed improved survival, while patients with high DNAM-1 expression before immunotherapy associated with unfavorable clinical outcome. The previously reported SNPs in NCR3 encoding NKp30, which purportedly influence mRNA splicing into isoforms with discrete functions, did not affect outcome in this study. Our results imply that variation in genes encoding activating NK cell receptors determine receptor expression and clinical outcome in AML immunotherapy.